2017
DOI: 10.5376/mpb.2017.08.0003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability on Tolerance of Maize (<i>Zea mays</i> L.) Genotypes Induced with Sodium Azide Mutagen

Abstract: variability on tolerance of maize (Zea mays L.) genotypes induced with sodium azide mutagen, Molecular Plant Breeding, 8(3): 27-37 (doi: 10.5376/mpb.2017.08.0003) Abstract This study investigated the mutagenic variability of maize (Zea mays L.) genotypes induced with sodium azide (NaN3).The seeds of maize genotypes; TZE-WDTSTR C4, TZM 154, SAMMAZ 15, DTE-YSR BC3, EV99 QPM, DTSR COF2, TZM 146 and TZM 1441 were pre-soaked in distilled water for six hours before treated with 20ml of sodium azide at 35, 45, 55,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This could be as a result of the lethal effect caused by the mutagen. Similar reductions were also observed in maize in the reports made by Olawuyi and Okoli (2017). Note: * = significant at p<0.05, ** = highly significant at p<0.01, *** = highly significant at p<0.001…”
Section: Resultssupporting
confidence: 82%
“…This could be as a result of the lethal effect caused by the mutagen. Similar reductions were also observed in maize in the reports made by Olawuyi and Okoli (2017). Note: * = significant at p<0.05, ** = highly significant at p<0.01, *** = highly significant at p<0.001…”
Section: Resultssupporting
confidence: 82%
“…Moreover, it was commonly utilized to induce mutagenesis in in vitro plant systems (Türkoğlu et al, 2022). Also, numerous studies have demonstrated the role and effectiveness of sodium azide to in enhance crop resistance against abiotic and biotic stresses (Olawuyi and Okoli, 2017;Hussain et al, 2022). Hussain et al (2022) reported that sodium azide treatments induced point mutations in the genome of plant, resulting in the production of proteins with different functions compared to non-mutant plants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, chemical mutagens have now become useful tools in crop improvement. Studies have shown the potential of mutagens in producing varieties tolerant or resistance to abiotic and biotic stresses in various susceptible crops while improving their yield and quality traits ( Olawuyi and Okoli, 2017 ). To date, several mutagens, including NaN 3 are being adapted for crop improvement with positive and negative effects ( Heslot, 1977 ).…”
Section: Introductionmentioning
confidence: 99%